PERCENTAGE OF PEST ATTACKS OF Spodoptera frugiperda J.E Smith (Lepidoptera: Noctuidae) ON SWEET CORN IN TOMOHON CITY. - Pebryna Haryanti Sinaga; James Kaligis; Elisabeth Rita M. Meray (Sam Ratulangi University, 2022)
This study aims to determine the percentage of pest attacks Spodoptera frugiperda J.E Smith on sweet corn plantations in the city of Tomohon. The results of this study are expected to provide information about the percentage of pests that attack S. frugiperda in the city of Tomohon as input for best-controlling pests. This research was conducted in the city of Tomohon, for 3 months starting from May July 2021. The research was carried out in three locations, namely in Woloan Village (West Tomohon), Kakaskasen II Village (North Tomohon), and Paslaten Village (East Tomohon). The location criteria used in this study is the sweet corn planted area of 0.5 ha at each research location. The research was conducted by survey method. Sampling was carried out using the diagonal slice method, and at each research location, it was divided into 4 parts, each part consisting of 5 sub-plots. Each subplot consists of 40 clumps of sweet corn plants. The data obtained were analyzed using descriptive quantitative analysis data. The results obtained in the field have the highest percentage in Kelurahan Woloan 90.75%, then followed by Kelurahan Paslaten at 13.25%, and the lowest percentage is in Kelurahan Kakaskasen II 11.37%Keywords: pests, sweet corn, WoloanAbstrakPenelitian ini bertujuan untuk mengetahui persentase serangan hama Spodoptera frugiperda J.E Smith pada tanaman jagung manis di kota Tomohon. Hasil penelitian ini diharapkan dapat memberikan informasi mengenai persentase serangan hama S. frugiperda di kota Tomohon sebagai masukan pengendalian hama terbaik. Penelitian ini dilaksanakan di Kota Tomohon, selama 3 bulan terhitung sejak Mei-Juli 2021. Penelitian dilakukan di tiga lokasi, yaitu di Desa Woloan (Tomohon Barat), Desa Kakaskasen II (Tomohon Utara), dan Desa Paslaten ( Tomohon Timur). Kriteria lokasi yang digunakan dalam penelitian ini adalah areal tanam jagung manis seluas 0,5 ha di setiap lokasi penelitian. Penelitian dilakukan dengan metode survei. Pengambilan sampel dilakukan dengan metode irisan diagonal, dan pada setiap lokasi penelitian dibagi menjadi 4 bagian, masing-masing bagian terdiri dari 5 anak petak. Setiap anak petak terdiri dari 40 rumpun tanaman jagung manis. Data yang diperoleh dianalisis dengan menggunakan analisis data deskriptif kuantitatif. Hasil yang diperoleh di lapangan memiliki persentase tertinggi di Kelurahan Woloan 90,75%, kemudian disusul Kelurahan Paslaten 13,25%, dan persentase terendah di Kelurahan Kakaskasen II 11,37%.Kata kunci: hama, jagung manis, Woloan